The Political Costs of Reforms : Fear or Reality? - Ciminelli, Gabriele (Staff Discussion Notes; Staff Discussion Notes, 2019)
The aim of this SDN is to examine whether fear of a political cost associated with economic reforms is justified by the available evidence, and whether there are lessons from how economic policies might be adjusted to mitigate any political cost. The paper will be based on a new comprehensive database on structural reforms developed by RES, which covers a broad sample of advanced and developing economies over four decades, and incorporates regulations related to the real sector (labor, product markets, trade and the current account), and the financial sector (banking, securities markets and the capital account). The paper will address three questions. First, do reforms reduce the probability of a government getting reelected? Second, for which reforms are political costs particularly high? And third, can fiscal stimulus or other policies 'sweeten the pill,' and would favorable economic conditions or greater reform ownership raise the odds for reelection?